Autism spectrum disorders: current issues and future directions. (September 2022) - Gallagher, L.; McGrath, J.
Abstract: This edition of Irish Journal of Psychological Medicine is a Special Themed Issue on Autism Spectrum Disorders (ASD). Mental health services are not currently meeting the needs of autistic people across the lifespan. We have limited evidence based treatments for core symptoms and comorbidities and there is lack of awareness and under-recognition of ASD, particularly in adults and certain groups of individuals. The key themes in this edition focus on challenges with recognition and diagnosis and address these from both clinical and research perspectives. Co-occurring conditions also feature, which are also under-recognised and can contribute to less optimal outcomes. New and existing research developments in stratification for clinical trials and neuroimaging are also discussed. We hope this Issue highlights relevant current issues in ASD, and provides insights which can help address the challenges in providing evidence based pathways to better meet the needs of autistic people into the future.